Message - Al-Shamahy, Prof. Dr. Hassan Abdulwahab (Universal Journal of Pharmaceutical Research, 2019)
Universal Journal of Pharmaceutical Research (UJPR) is a scientific project will assist a in resolution health problems not only in developing countries but also worldwide; and I am contributed in this project under the guidance of the Editor-in-Chief and the other board members. Enduring is the key of the success accordingly congratulation to all editorial board members for their high success of today through their hard work and persistence for 3 years. The journal successfully completed 3 Yrs (Total 15 issues), 154 articles of different authors from different countries including Nigeria, Yemen, India, Cameroon, Egypt, China, Pakistan, Iran, USA, West Indies, Iraq, Malaysia and Nepal. Hence UJPR is an international journal without suspicion and indexed in more than 30 locations is other value of UJPR as an international journal. The future of the journal will be brilliant with achievement an impact factor and to be member of Scopus and ISI journals but all of that need hardworking from journal members and authors. Therefore, I will take this occasion to urge all authors to prepare their manuscripts strictly according to journal instructions so as to avoid any undue delay in its editorial processing and disappointment of rejection.